2015
DOI: 10.15516/cje.v17i0.1073
|View full text |Cite
|
Sign up to set email alerts
|

Examples from Visual Surroundings as an Incentive for Children with Mild Intellectual Disability to Express their Creativity in the Art Domain/Primjeri iz vizualnog okruženja kao poticaj kreativnih sposobnosti kod djece s blažim intelektualnim teškoćama

Abstract: In getting to know the nature of children's creative expression, we talk ever less about teaching creativity and more about the ways of stimulating, and the conditions that ought to be provided for creativity to be manifested. The aim of this work is to determine the difference in creative abilities of children with mild intellectual disability (MID) before and after visual prompting in the process of creating an art drawing. Creativity was assessed on a sample of 69 subjects, using the Test for creative think… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…People with intellectual disabilities have been shown to be creative in their humor use (Johnson et al, 2012 ). People with autism and intellectual disabilities, who have been found to display less playful pretending (Hobson et al, 2009 ), have demonstrated the ability, with prompting, to enhance their humorous creativity (Gagić et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…People with intellectual disabilities have been shown to be creative in their humor use (Johnson et al, 2012 ). People with autism and intellectual disabilities, who have been found to display less playful pretending (Hobson et al, 2009 ), have demonstrated the ability, with prompting, to enhance their humorous creativity (Gagić et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…(Gagić et al, 2015 ) used humorous content as an indicator of the expression of creative ability in a drawing task. They used a method of prompting to encourage creative thinking around the art and showed an increase in the humor within the work, post prompting.…”
Section: Resultsmentioning
confidence: 99%
“…Dans ce contexte, nous considérons que la créativité enfantine doit être conçue comme une créativité personnelle, dépourvue de la composante environnementale et limitée aux composantes cognitives et comportementales. Elle doit être considérée en ayant recours aux critères d 'originalité et d'utilité (Runco, 2011), du fait que ces deux critères apparaissent dans les définitions de la plupart des recherches étudiant la créativité (Gagić et al, 2015).…”
Section: La Créativité Enfantineunclassified
“…Hudenko, Stone, and Bachorowski concluded that children with ASD laugh in response to internal positive states, whereas typically developing children also use laughter to negotiate social scenarios [51]. Gagi, Japunda-Milisavljevi, and uri-Zdravkovi suggested that when prompting students with ASD, students may engage in and enhance their humorous activity [52]. The purpose of the current study is to explore how paralinguistic cues (i.e., facial expressions, intonation/prosody), affective expression, and social context skills develop across the lifetime in students who are typically developing and students with ASD, AS, or pragmatic language disorder (PLI).…”
Section: Social Context Appraisalmentioning
confidence: 99%